The Effectiveness of Sports Open Spaces in Facilitating Community Sports Activities During the Covid-19 Pandemic in Tegal District (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
During the pandemic some people in Tegal district only spend time at home to work and study virtually, this makes it difficult to exercise for several reasons, physical activity is very important for everyone of all ages. The availability of open sports spaces that are easily accessible to all levels of society can encourage the creation of a society who likes to exercise or do physical activities. This research was conducted using a qualitative approach. The results of the study and analysis will later be able to describe and explain the facts of the state of open sports spaces. Based on the results of interviews and observations. This is indicated by the important points in spatial planning as stipulated in Law No. 26 of 2007 concerning Spatial Planning that has not been fully implemented. The utilization of sports open space planning in Tegal Regency has been maximized for its mechanism, but its development and development has not met its effectiveness. Region of Tegal Regency in 2012-2032. However, the control over the use of open space and sports open space in Tegal Regency has not been carried out optimally, based on the results of observations of the rules for the use of sports open spaces for other activities in the sample sub-districts, and there is no direct involvement of related parties in supervising and maintaining the space. open and open sports spaces that are often used for people to exercise. The phenomenon of the participation rate of community recreational sports activities in Tegal Regency shows a decrease from before the pandemic, the community is very enthusiastic about doing sports activities carried out on holidays or free time and sports activities are carried out in groups with friends, family, or the community.